Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales. (5th October 2022) - Ryan, John P.; Benoit‐Bird, Kelly J.; Oestreich, William K.; Leary, Paul; Smith, Kevin B.; Waluk, Chad M.; Cade, David E.; Fahlbusch, James A.; Southall, Brandon L.; Joseph, John E.; Margolina, Tetyana; Calambokidis, John; et al.
Abstract: Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics. Abstract : The movements of blue whales off central California, monitored through the sounds they produce, reveal that Earth's largest animals closely track a specific type of circulation. This circulation results from wind‐driven upwelling, and within this circulation the prey of blue whales form dense aggregations that greatly increase energy intake by foraging whales. The patterns of blue whale movement also reveal a key threat to this endangered species: risk of mortality from ship strikes.